Climate Change and the Health Sector Healing the World - Thomas, Alexander; Reddy, K. Srinath; Alexander, Divya; Prabhakaran, Poornima (Taylor & Francis, 2022)
The health sector is known to be one of the major contributors towards the greenhouse gas emissions causing the climate crisis, the greatest health threat of the 21st century. This volume positions the health sector as a leader in the fight against climate change and explores the role of the health system in climate policy action. It delivers an overview of the linkages between climate change and the health sector, with chapters on the impact of climate change on health, its connection to pandemics, and its effects on food, nutrition and air quality, while examining gendered and other vulnerabilities. It delves into the different operational aspects of the health sector in India and details how each one can become climate-smart to reduce the health sector's overall carbon footprint, by looking at sustainable procurement, green and resilient healthcare infrastructure, and the management of transportation, energy, water, waste, chemicals, pharmaceuticals and plastics in healthcare. Well supplemented with rigorous case studies, the book will be indispensable for students, teachers, and researchers of environmental studies, health sciences, and climate change. It will be useful for healthcare workers, public health officials, healthcare leaders, policy planners, and those interested in climate resilience and preparedness in the healthcare sector.